2020
DOI: 10.7759/cureus.7463
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Maternal Age and the Prevalence of Congenital Heart Disease in Newborns from 2016 to 2018 in Single Cardiac Center in Jeddah, Saudi Arabia

Abstract: Congenital heart diseases (CHD) are suggested to be associated with advanced maternal age in different ethnicities and geographical locations. To provide a profound ground for comparison with Saudi Arabian population, in this study, we have assessed the association between maternal age and congenital heart diseases for different age groups during the period from 2016 to 2018 in King Abdul-Aziz Medical City in Jeddah. In this case-control study, we found no evidence relating maternal age to the incidence of CHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Further, the study indicated that ASD is the most frequent type of CHD among our participants followed by VSD. Similar findings were also reported from several regional and global studies [9][10][11][12][13]. In contrast, in one local study, VSD was the most evalent diagnosis among cases with CHD [14].…”
Section: Fig 5 the Outcome Of Patients With Chd (Cyanotic And A Cyasupporting
confidence: 88%
“…Further, the study indicated that ASD is the most frequent type of CHD among our participants followed by VSD. Similar findings were also reported from several regional and global studies [9][10][11][12][13]. In contrast, in one local study, VSD was the most evalent diagnosis among cases with CHD [14].…”
Section: Fig 5 the Outcome Of Patients With Chd (Cyanotic And A Cyasupporting
confidence: 88%
“…Interestingly, even though previous studies did not report an association between total CHD and maternal age, some did report an association of maternal age and specific CHD subtypes (Hashim et al, 2020; Miller et al, 2011). Specifically, based on our subgroup analysis, we found a positive association of ASD, PVS, CoA, ToF phenotypes with advanced maternal age.…”
Section: Discussionmentioning
confidence: 92%
“…Opposite to this observation, our population was free of chromosomal anomalies and shown to have this significant relation between the maternal age and TGA. Locally, Hashem et al 41 reported an insignificant association between the overall CHD risk and mean maternal age, but when they did a sub-analysis for the sample, VSD and PDA were associated with maternal age >35 years, while the other lesions did not reach that significance. Their lack of significance was attributed to the low statistical power of their sample size.…”
Section: Discussionmentioning
confidence: 92%